Gait analysis as a robust pain behavioural endpoint in the chronic phase of the monoiodoacetate-induced knee joint pain in the rat. Issue 1 (February 2022) - Han, Felicity Y.; Brockman, David A.; Nicholson, Janet R.; Corradini, Laura; Smith, Maree Therese
Abstract : The monoiodoacetate-induced rat model of osteoarthritis knee pain is widely used. However, there are between-study differences in the pain behavioural endpoints assessed and in the dose of intraarticular monoiodoacetate administered. This study evaluated the robustness of gait analysis as a pain behavioural endpoint in the chronic phase of this model, in comparison with mechanical hyperalgesia in the injected (ipsilateral) joint and development of mechanical allodynia in the ipsilateral hind paws. Groups of Sprague–Dawley rats received a single intraarticular injection of monoiodoacetate at 0.5, 1, 2 or 3 mg or vehicle (saline) into the left (ipsilateral) knee joint. An additional group of rats were not injected (naïve group). The pain behavioural methods used were gait analysis, measurement of pressure algometry thresholds in the ipsilateral knee joints, and assessment of mechanical allodynia in the ipsilateral hind paws using von Frey filaments. These pain behavioural endpoints were assessed premonoiodoacetate injection and for up to 42-days postmonoiodoacetate injection in a blinded manner. Body weights were also assessed as a measure of general health. Good general health was maintained as all rats gained weight at a similar rate for the 42-day study period. In the chronic phase of the model (days 9–42), intraarticular monoiodoacetate at 3 mg evoked robust alterations in multiple gait parameters as well as persistent mechanical allodynia in the ipsilateral hind paws. For the chronic phase of the monoiodoacetate-induced rat model of osteoarthritis knee pain, gait analysis, such as mechanical allodynia in the ipsilateral hind paws, is a robust pain behavioural measure.